Introduction to educational measurement - Noll, Victor H. (Boston : Houghton Mifflin, 1965)
In the interval since publication of the first edition of this volume, much has happened in the field of measurement. The Use of test in the schools has increased and users have become more knowledgeable. In addition, testing has become a somewhat controversial issue. These fact, plus the warm response received by the first edition, have prompted author and publisher to produce a thorough revision that will meet current needs and interest.
1. Educational measurement: an overview -- 2. The Development of educational management -- 3. A Little statistics -- 4. Finding and selecting good measuring instrument -- 5. Objectives as the basis of all good measurement -- 6. Planning and constructing the Teacher-made test -- 7. Trying out and evaluating the teacher-made test -- 8. Measuring achievement in the elementary grades -- 9. Measuring achievement in the secondary grades -- 10. The Measurement of capacity: general intelligence -- 11. The Measurement of capacity: special aptitudes -- 12. The Measurement of personality and adjustment: self-report techniques --13. The Measurement of personality and adjustment: observational techniques -- 14. The Measurement program -- 15. Using the results of measurement.
Includes bibliographical references and index.
Keywords: EDUCATIONAL MANAGEMENT; EDUCATIONAL TEST AND MEASUREMENTS